Investigating novice doctors' reflections in debriefings after simulation scenarios. (4th May 2015) - Kihlgren, Per; Spanager, Lene; Dieckmann, Peter
Abstract: Background : Debriefing is pivotal to the simulation learning process, and the reflection that it aims to foster is fundamental in experiential learning. Despite its importance, essential aspects of debriefing remain unclear. Study objective : To investigate reflection in debriefings by assessing participants' reflection levels in discussions of leader/follower-ship or role distribution and compare occurrences of high reflection with those of lower reflection. Methods : The data consisted of videos from 38 debriefings with 10 debriefers from the Danish Institute of Medical Simulation. An adapted framework of reflection levels was used for the analysis. A comparison was made between debriefers' utterances across occurrences of higher and lower reflection. Results : Participants reached only lower reflection levels. Of five reflection levels, the second was reached the most frequently and the third was the highest reached. No salient differences were found in debriefers' utterances across occurrences of higher and lower reflection. Conclusion : Participants' reflection levels were low in this cohort of novice doctors training leadership skills in acute situations. However, the desired reflection should be appropriated to the given context. The rating of reflection levels is a promising approach to analyze reflection in conversation in experience-based learning situations.